The Role of Glycation on the Aggregation Properties of IAPP - Milordini, Giulia; Zacco, Elsa; Percival, Matthew; Puglisi, Rita; Dal Piaz, Fabrizio; Temussi, Pierandrea; Pastore, Annalisa (Frontiers in Molecular Biosciences, 2020)
Epidemiological evidence shows an increased risk for developing Alzheimer disease in people affected by diabetes, a pathology associated with increased hyperglycaemia. A potential factor that could explain this link could be the role that sugars may play in both diseases under the form of glycation. Contrary to glycosylation, glycation is an enzyme-free reaction that leads to formation of toxic advanced glycation end-products (AGEs). In diabetes, the islet amyloid polypeptide (IAPP or amylin) is found to be heavily glycated and to form toxic amyloid-like aggregates, similar to those observed for the Aβ peptides, often also heavily glycated, observed in Alzheimer patients. Here, we studied the effects of glycation on the structure and aggregation properties of IAPP with several biophysical techniques ranging from fluorescence to circular dichroism, mass spectrometry and atomic force microscopy. We demonstrate that glycation occurs exclusively on the N-terminal lysine leaving the only arginine (Arg11) unmodified. At variance with recent studies, we show that the dynamical interplay between glycation and aggregation affects the structure of the peptide, slows down the aggregation process and influences the aggregate morphology.